Impact of European Union programs on the activities of the Third Polish Republic's Parliament in the field of sport in the years 2004-2007 - Leonard Nowak; Maria Alicja Nowak (Wydawnictwo Naukowe Uniwersytetu Szczecińskiego, 2021)
The aim of this paper is to show the impact of European Union programs on the activities of the Third Polish Republic's Parliament in the field of sport in the years 2004-2007. The Republic of Poland joined the European Union (EU) on 1 May 2004. Since then, it has been co-creating the image of sport in Europe. All activities undertaken by the Polish Parliament in the development of sport after this event were related to programs in the European Union. During the period covered in this paper, the institutions involved in sport in the European Union included the Council of the European Union, the European Parliament, the European Commission and the European Court of Justice. One year after Poland's accession to the European Union, elections were held for the fifth term of the Polish Sejm (2005-2007). The representatives of the Polish Parliament, during meetings of the Physical Culture and Sport Committee, repeatedly pointed to the possibility of adapting EU programs and their use in the development of sport in Poland. The material presented by the Ministry of Sport and the Office of the European Integration Committee in Warsaw informed about the following programs (mainly investment ones): Sport in the structures of the European Union and European Union Programs for the development of sport, implemented between 2004 and 2006. The most important issues raised by the Committee were those contained in the two most important documents: White Paper on Sport and Independent European Sport Review. As a result of the work of the Parliament of the Republic of Poland during the fifth term of office (2005-2007) in cooperation with the Ministry of Sport and the Parliamentary Physical Culture and Sport Committee, a plan for co-financing projects for the construction, extension or modernization of sports infrastructure under the EU structural programs and the INTERREG III A and EQUAL Community Initiatives was developed. The effect of Poland's membership in the EU in that period was a gradual elimination of infrastructural negligence and undertaking activities related to the activation of local communities in the area of education and sport. Poland's membership in the EU so far has brought positive results: increased accessibility of sport thanks to the development of regional infrastructure co-financed by the EU funds and the enrichment of the program offer by supporting projects related to the organization of extracurricular sports activities for children and young people. The positive effects of membership in the field of sport are still being perceived by selected groups and society as a whole.